(untitled) (Bangladesh Medical Journal, 2016)
The patients with essential hypertension are increasing in our country and all over the world. Insulin secretion by the pancreatic beta cells may be increased in several metabolic disorders including glucose intolerance, dyslipidemia and essential hypertension. Many studies suggested an association between essential hypertension and defective insulin secretion. So, insulin secretory capacity may act as important clinical and biochemical determinant which will provide further information to minimize hypertension related other complications. This study was aimed to assess insulin secretory capacity in adult male with essential hypertension. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2012 to June 2013. A total number of one hundred fifty male subjects were selected with age ranging from 25 to 45 years. Among them, seventy five male essential hypertensive subjects were included in the study group. The study subjects were selected from Out- patient Department of Medicine, Dhaka Medical College Hospital. Age matched 75 apparently healthy males were studied as control group (A) for comparison. or the calculation of insulin secretory capacity, fasting serum insulin level was measured by ELISA method and fasting serum glucose by glucose oxidase method in the laboratory of Department of Physiology and Molecular Biology, BIRDEM Academy, Dhaka.In this study, 134 insulin secretory capacity (HOMA%B) was significantly higher in essential hypertensive male patients than those of the control subjects. It was seen that essential hypertension has positive and significant relationship with insulin secretory capacity. Bangladesh Med J. 2014 Sep; 43 (3): 134-137